(untitled) (Research, Society and Development, 2020)
The present study aimed to carry out an integrative review of the literature regarding depression and associated factors in students, mainly from higher education. The Scielo data base was accessed through the descriptors "depression" and "students" with the help of the Boolean operator "and", adding the filters "Brazil" and "last five years" (2016-2020). The search resulted in 18 articles, whose content was organized into a single textual corpus, and was submitted to a Descending Hierarchical Classification (CHD). 44% (8) of the studies found were carried out in the Southeast, 44% 8 recruited medical students in their methodology, 5 exclusively with medical students. Only one of the studies that specified the courses to be listed, sought to analyze courses that were not in the health area, such as pedagogy, administration, economics, pharmacy-biochemistry, process engineering and biotechnology. Aggravating factors of depression are lifestyle, course, interpersonal relationships and personal variables. Mitigating factors found were religiosity and professional experience.